2020
DOI: 10.1017/s095653612000036x
|View full text |Cite
|
Sign up to set email alerts
|

Ally, Client, or Outpost? Evaluating the Relationship Between Xunantunich and Naranjo in the Late Classic Period

Abstract: Investigations at Xunantunich indicate that this major Belize River Valley site rose rapidly to regional prominence during the Late Classic Hats' Chaak phase (a.d. 670–780). While the social, political, and economic reasons for Xunantunich's relatively late and rapid rise are still not fully understood, it has been suggested that this ascent was a direct result of either a patron-client relationship with, or owing to direct control by, the larger primary center of Naranjo in neighboring Guatemala. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Xunantunich was a major center that overlooked the Mopan River before its confluence with the Macal River. Although first settled in the Early and Middle Preclassic periods (~1200–900 BCE), following a brief occupational hiatus the site was re-established as the capital of a large Late Classic Belize Valley polity [ 151 – 155 ]. All burials in this study [previously published, see 156 ] derive from the site’s monumental core except for one dating to the Late Classic from San Lorenzo (Op.…”
Section: Eastern Maya Lowlands Regional Backgroundmentioning
confidence: 99%
“…Xunantunich was a major center that overlooked the Mopan River before its confluence with the Macal River. Although first settled in the Early and Middle Preclassic periods (~1200–900 BCE), following a brief occupational hiatus the site was re-established as the capital of a large Late Classic Belize Valley polity [ 151 – 155 ]. All burials in this study [previously published, see 156 ] derive from the site’s monumental core except for one dating to the Late Classic from San Lorenzo (Op.…”
Section: Eastern Maya Lowlands Regional Backgroundmentioning
confidence: 99%
“…Elsewhere, some smaller political centers took advantage of the weakened positions of their previously dominant overlords. For example, the site of Xunantunich experienced a short florescence at the end of the Late Classic period in the wake of dynastic struggles at Naranjo, a polity that previously held a dominating role in eastern Peten and western Belize (Awe et al 2020;LeCount and Yaeger 2010a;LeCount et al 2002). LeCount's (1999) analysis of the distribution of fine ware and exotic ceramics across different architectural groups at the site revealed that inequalities were most evident during the Late Classic II phase, but that this differential access disappeared during the Terminal Classic.…”
Section: Social Status Changes In the Maya Lowlands During The Late Classic And Terminal Classic Periodsmentioning
confidence: 99%
“…It also runs contrary to elite Maya tradition which placed great emphasis on situating rulers' residences in places where they emanated power and prestige manifested by their sheer size and monumentality (see Awe 2008). It is therefore more likely that the construction of the north palace complex was associated with an effort to provide additional living space for the ever-growing royal family, "or with increasing administration, courtly prerogatives, and the individual motivations of particular monarchs" at the site (Awe et al 2020). Additionally, while Yaeger (2010: 156) suggests Plaza A-III was abandoned between ~CE 750-775, new evidence at Structure A13 in the form of a hieroglyphic date etched into the building's surface (presented below), suggests a slight extension of the Plaza A-III occupation to CE 790 (Watkins et al 2018).…”
Section: Xunantunichmentioning
confidence: 99%